Associations of maternal insulin sensitivity during pregnancy with childhood central adiposity in the Genetics of Glucose regulation in Gestation and Growth (Gen3G) cohort. Issue 2 (11th October 2022) - Ghildayal, Nidhi; Allard, Catherine; Blais, Kasandra; Doyon, Myriam; Arguin, Melina; Bouchard, Luigi; Perron, Patrice; Hivert, Marie‐France
Summary: Background: Childhood obesity has been associated with prenatal exposure to maternal hyperglycaemia, but we lack understanding about maternal insulin physiologic components that contribute to this association. Objectives: Evaluate the association between maternal insulin sensitivity during pregnancy and adiposity measures in childhood. Methods: In 422 mother–child pairs, we tested associations between maternal insulin sensitivity measures at 26 weeks of pregnancy and child adiposity measures, including dual‐energy X‐ray absorptiometry body composition and anthropometry (body mass index and waist circumference) at 5 years. We used linear regression analyses to adjust for maternal age, ethnicity, gravidity, first‐trimester body mass index, and child sex and age at mid‐childhood. Results: In early pregnancy, maternal mean age was 28.6 ± 4.3 years and median body mass index was 24.1 kg/m 2 . Lower maternal insulin sensitivity indices were correlated with greater child adiposity based on anthropometry measures and on dual‐energy X‐ray absorptiometry total and trunk % fat in univariate associations (r = −0.122 to −0.159). Lower maternal insulin sensitivity was specifically associated with higher dual‐energy X‐ray absorptiometry trunk % fat ( n = 359 for Matsuda; β = −0.034 ± 0.013; p = 0.01) after adjustment for covariates, including maternal body mass index. Conclusions: Maternal insulin sensitivity during pregnancy may contribute to increased risk for higher offspring central adiposity in middle childhood.